Answer:
Emil's back pack weigh now
.
Explanation:
Given:
Total Weight of backpack =
can be Rewritten as
Weight of backpack =
Weight of Book 1 =
Weight of Book 2 =
We need to find weight of back pack after removing books.
Solution:
Now we can say that;
weight of back pack after removing books can be calculated by Subtracting Weight of Book 1 and Weight of Book 2 from Total Weight of backpack.
framing in equation form we get;
weight of back pack after removing books =
Now to solve the equation we will first make the denominator common using LCM.
weight of back pack after removing books =
Now the denominators are common so we will solve the numerator.
weight of back pack after removing books =
Hence Emil's back pack weigh now
.